A review study of instantaneous electric energy transport theories and their novel implementations. (May 2016) - Beck, Y.; Calamaro, N.; Shmilovitz, D.
Abstract: Electric energy transport theories are still a debatable subject regarding their validity and applicability in various aspects. This paper includes a comparative study of the group of theories which are categorized as instantaneous theories as opposed to periodic-averaged ones. As a preliminary review this paper presents first the three apparent power definitions in order to emphasize the difference between them. A discussion regarding their accuracy for energy metering of various conditions such as multiphase and non-sinusoidal environments is presented. Instantaneous theories are then reviewed and compared with periodic averaged theories. The review focuses mainly on p-q theory ( PQT ) and its derivative, instantaneous multi-phase theory. The legacy application of this theory for active filtering is briefly presented and the new idea of using the theory for multi-load and multi-source theory is presented as well. The comparison identifies the similarities and differences between the instantaneous and periodic averaging theories, and their inter-relations.